Anti-inflammatory activity of superoxide dismutase mimics functionalized with cell-penetrating peptides. Issue 7 (5th February 2020) - Mathieu, Emilie; Bernard, Anne-Sophie; Ching, H. Y. Vincent; Somogyi, Andrea; Medjoubi, Kadda; Fores, Jennifer Rodon; Bertrand, Hélène C.; Vincent, Amandine; Trépout, Sylvain; Guerquin-Kern, Jean-Luc; Scheitler, Andreas; Ivanović-Burmazović, Ivana; et al.
Abstract : A superoxide dismutase mimic was functionalized with three peptides: -R9, -RRWWRRWRR or -Fx -r-Fx -K (MPP). They were studied in intestinal epithelial cells in an inorganic cellular chemistry approach: quantification, distribution and bio-activity. Abstract : A superoxide dismutase mimic (Mn1) was functionalized with three positively charged-peptides: RRRRRRRRR (Mn1-R9), RRWWWRRWRR (Mn1-RW9) or Fx -r-Fx -K (Mn1-MPP). Characterization of the physico-chemical properties of the complexes show that they share similar binding affinity for Mn 2+, apparent reduction potential and intrinsic superoxide dismutase activity. However, their accumulation in cells is different (Mn1-R9 < Mn1-MPP < Mn1-RW9 < Mn1), as well as their subcellular distribution. In addition, the three functionalized-complexes display a better anti-inflammatory activity than Mn1 when assayed at 10 μM. This improvement is due to a combination of an anti-inflammatory effect of the peptidyl moiety itself, and of the SOD mimic for Mn1-RW9 and Mn1-MPP. In contrast, the enhanced anti-inflammatory activity of Mn1-R9 is solely due to the SOD mimic.